2003
DOI: 10.1152/ajpheart.00774.2002
|View full text |Cite
|
Sign up to set email alerts
|

Oxytocinergic regulation of cardiovascular function: studies in oxytocin-deficient mice

Abstract: Oxytocin (OT) has been implicated in the cardiovascular responses to exercise, stress, and baroreflex adjustments. Studies were conducted to determine the effect of genetic manipulation of the OT gene on blood pressure (BP), heart rate (HR), and autonomic/baroreflex function. OT knockout (OTKO -/-) and control +/+ mice were prepared with chronic arterial catheters. OTKO -/- mice exhibited a mild hypotension (102 +/- 3 vs. 110 +/- 3 mmHg). Sympathetic and vagal tone were tested using beta(1)-adrenergic and chol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
40
0
2

Year Published

2003
2003
2019
2019

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 57 publications
(43 citation statements)
references
References 45 publications
1
40
0
2
Order By: Relevance
“…There is also evidence from rats that oxytocin can downregulate CRF gene expression in the PVN (Nomura et al, 2003). In addition, mice that are genetically deficient for either oxytocin (Michelini et al, 2003;Mantella et al, 2004) or the oxytocin receptor (Takayanagi et al, 2005) tend to be highly reactive to stressors.…”
Section: Discussionmentioning
confidence: 99%
“…There is also evidence from rats that oxytocin can downregulate CRF gene expression in the PVN (Nomura et al, 2003). In addition, mice that are genetically deficient for either oxytocin (Michelini et al, 2003;Mantella et al, 2004) or the oxytocin receptor (Takayanagi et al, 2005) tend to be highly reactive to stressors.…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies in oxytocin knockout mice have confirmed that these animals have abnormal autonomic and baroreflex control over heart rate (HR) and BP, and that female mice lacking oxytocin have increased anxiety-like behaviors (Mantella, Vollmer, Li, & Amico, 2003;Michelini, Marcelo, Amico, & Morris, 2003). Other recent research in both male and female animal models indicates that in addition to its production within the hypothalamus, oxytocin is produced and released in the heart and the vasculature, and that oxytocin specifically activates receptors that are present in both sites, leading to decreases in HR, contractile force and vascular resistance (Jankowski et al, 2000;Mukaddam-Daher, Yin, Roy, Gutkowska, & Cardinal, 2001;Thibonnier et al, 1999).…”
Section: Discussionmentioning
confidence: 99%
“…Although OT is well recognized for its role in reproduction, recent discoveries suggest that OT is also involved in regulation of fluid balance, blood pressure (BP), and cardiac function. [1][2][3][4] Oxytocinergic neurons innervate brain regions important in cardiovascular control, such as the nucleus tractus solitarius, locus ceruleus, dorsal motor nucleus of the vagus, and intermediolateral cell column in the spinal cord. [5][6][7] OT and OT receptors are present in the vasculature, heart, and kidney, 2 and OT has effects on BP, renal function, and salt intake.…”
mentioning
confidence: 99%
“…21 These animals also showed imbalances in autonomic control, an enhanced sympathetic reserve, and alterations in baroreflex function. 4 The present studies were designed to expand these findings in the OTKO model: (1) to determine the effect of volume depletion on salt and water intake; (2) to determine the effect of central Ang II stimulation on salt and water intakes; and (3) to determine baseline BP and the response to central Ang II. Volume depletion was produced by PEG treatment, which activates neural and endocrine reflexes, resulting in enhanced intake of salt and water to compensate for fluid losses.…”
mentioning
confidence: 99%